Portaria PRSP nº 292, de 19 de março de 2013 - Anamara Osorio Silva (DMPF-e, Brasília, DF, n. 17, 26 mar. 2013. Administrativo, p. 21., 2013)
Dispensa e designação de servidor para exercer Função de Confiança